Antifatigue effects of anshenyizhi compound in acute excise‐treated mouse via modulation of AMPK/PGC‐1α‐related energy metabolism and Nrf2/ARE‐mediated oxidative stress. Issue 6 (25th May 2020) - Peng, Xiaoming; Gao, Li; Aibai, Silafu
Abstract: The anshenyizhi compound (AC), a mixture from Chinese medicine herbs, has numerous biological effects. In the present study, the acute exercise‐treated mice model was established to explore the antifatigue properties of AC and its underlying mechanisms. AC increased exercise endurance in the weight‐loaded forced swimming test and rota‐rod test. The antifatigue properties of AC were closely correlated with enhancing the body's exercise endurance by increasing the levels of cyanmethemoglobin, testosterone/corticosterone, and creatine kinase, while decreasing the levels of lactic acid, lactate dehydrogenase, and blood urea nitrogen in serum. Moreover, our results confirmed the antioxidant ability of AC by improving the activities of superoxide dismutase while reducing reactive oxygen species and malondialdehyde levels in serum. The AC also improved the storage of glycogen by increasing the levels of succinate dehydrogenase, and malate dehydrogenase in liver and muscle. Additionally, AC displayed the antifatigue and antiapoptosis effects via regulating Nrf2‐mediated oxidative stress, AMPK‐related glucose metabolism, and p53 pathways. Our experimental results first provided a support that AC had effects on antifatigue through regulating AMPK/PGC‐1α‐related energy metabolism and Nrf2/ARE‐mediated oxidative stress. Consequently, AC could be developed into a new functional food supplement for the prevention and treatment of diseases related to fatigue in the future.